The Influence Of Attraction, Amenities, And Accessibility On Interest In Returning To Visit The Snake Palace Cave Destination, West Manggarai Regency - Daria Alviota Hamat; Aprilia Rachmadian; Ani Puspawigati (Jurnal Penelitian, 2026)
This study aims to analyze the influence of attractions, amenities, and accessibility on tourists’ intention to revisit the Snake Palace Cave destination in West Manggarai Regency. The research employed a quantitative approach with an explanatory research design. A total of 105 respondents were selected using purposive sampling, consisting of tourists who had visited Snake Palace Cave and were at least 17 years old. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The results indicate that attractions and accessibility have a positive and significant effect on tourists’ revisit intention, while amenities do not have a significant effect. Simultaneously, the three variables explain 61.8% of the variance in revisit intention. These findings suggest that the uniqueness of the destination, including the natural snake habitat and traditional snake-calling ritual, is the main factor encouraging tourists to revisit, supported by convenient access to the destination. This research contributes theoretically by strengthening the 3A concept (Attractions, Amenities, Accessibility) in the development of nature- and culture-based tourism destinations. Practically, the findings provide recommendations for destination managers and local governments to improve tourism management quality, particularly in enhancing accessibility and preserving local cultural attractions.